Features of peripheral circulation in young people of different somatotype with normal and high blood pressure - S. N. Vadzyuk; L. I. Horban; I. Ya. Papinko; W. Zukow (Kazimierz Wielki University, 2019)
Introduction: Hypertension is the most common disease of the circulatory system. The most relevant area in the assessment of individual human health is the constitutional approach. Many studies have shown that most indicators of the blood circulation are related to anthropometric parameters of the body, which is why studying the features of peripheral hemodynamics in representatives of different somatotypes with normal and high blood pressure is especially relevant. The purpose of the study was to determine the features of peripheral circulation in young people, aged 18 to 22 years, of different somatotype with normal and high blood pressure. Materials and methods: two groups of subjects selected: a control group (CG) - those in which the value of BP consistent optimum level by the WHO classification (125 people), the second group - those in which systolic blood pressure higher than 130 mmHg and (or) diastolic - 85 mmHg (135 people). Somatotyping performed using techniques by Carter and Heath. To study the condition of peripheral hemodynamics used rheovasography of the lower extremities. Results and discussion: statistical analysis of the results by the Kruskal-Wallis method in the individuals of both groups showed a significant difference in the majority of rheovasography indices among subjects of different somatotypes. The method of multiple comparisons showed significant differences in the values of peripheral circulation among representatives of different somatotypes with normal and high blood pressure. Conclusions: peripheral hemodynamics in subjects with normal blood pressure and predominance of the endomorphic component was characterized by significantly higher vascular tone of mainly medium and small diameter compared to ectomorphs. The peripheral circulation of individuals with high blood pressure and predominance of the endomorphic component, compared to ectomorphs and to lesser extent mesomorphs, was characterized by a significantly higher increase in the tone of the small arteries and a decrease in the tone of the large arteries.